Implementation Of Restorative Justice By The Indonesian National Police After The Enforcement Of Article 70 Of Law Number 1 Of 2023 On The Criminal CodeE - Kamagi, Rendy Cristian; Budisetyowati, Dwi Andayani; Sugeng, Sugeng (Fakultas Hukum Dehasen, 2025)
Indonesian National Police Regulation Number 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice has regulated police authority. This regulation was established as it is indeed necessary for the police to serve as a guideline in handling criminal acts through a restorative justice mechanism. The establishment of this regulation further emphasizes that the discretion provision in Article 18 of Law Number 2 of 2002 is highly urgent and needed in law enforcement practices. Repressive law enforcement efforts are increasingly considered less effective. The research problem formulated includes: First, what is the meaning of restorative justice as a complaint offense under Article 70 of Law Number 1 of 2023? Second, how is the implementation of restorative justice determination as a complaint offense at the level of authority within the Indonesian National Police? This study employs a normative juridical research method. The findings indicate that the application of restorative justice by law enforcement officials remains inconsistent, with varying interpretations at different stages, including investigation, prosecution, and trial processes. A review of the implementation of restorative justice for children in the Mojokerto District Court Decision Number: 11/Pid.Sus-Anak/2023/PN Mjk serves as an example of such inconsistencies. This issue arises due to the absence of explicit restorative justice provisions within the Indonesian Criminal Code (KUHP). The enactment of Law Number 1 of 2023 further reinforces Indonesian National Police Regulation Number 8 of 2021. The implementation of restorative justice determination for complaint offenses at the level of police authority following the enforcement of Article 70 of Law Number 1 of 2023 also stipulates the conditions under which restorative justice may be granted. The application of Article 70 of Law Number 1 of 2023, when aligned with Article 18 of Law Number 2 of 2002, grants police discretion to apply restorative justice in a manner that can be integrated with public interest considerations, particularly those oriented toward fines.